Oxyradical Stress, Endocannabinoids, and Atherosclerosis - Anberitha T. Matthews; Matthew K. Ross (Toxics, 2015)
Atherosclerosis is responsible for most cardiovascular disease (CVD) and is caused by several factors including hypertension, hypercholesterolemia, and chronic inflammation. Oxidants and electrophiles have roles in the pathophysiology of atherosclerosis and the concentrations of these reactive molecules are an important factor in disease initiation and progression. Overactive NADPH oxidase (Nox) produces excess superoxide resulting in oxidized macromolecules, which is an important factor in atherogenesis. Although superoxide and reactive oxygen species (ROS) have obvious toxic properties, they also have fundamental roles in signaling pathways that enable cells to adapt to stress. In addition to inflammation and ROS, the endocannabinoid system (eCB) is also important in atherogenesis. Linkages have been postulated between the eCB system, Nox, oxidative stress, and atherosclerosis. For instance, CB2 receptor-evoked signaling has been shown to upregulate anti-inflammatory and anti-oxidative pathways, whereas CB1 signaling appears to induce opposite effects. The second messenger lipid molecule diacylglycerol is implicated in the regulation of Nox activity and diacylglycerol lipase β (DAGLβ) is a key biosynthetic enzyme in the biosynthesis eCB ligand 2-arachidonylglycerol (2-AG). Furthermore, Nrf2 is a vital transcription factor that protects against the cytotoxic effects of both oxidant and electrophile stress. This review will highlight the role of reactive oxygen species (ROS) in intracellular signaling and the impact of deregulated ROS-mediated signaling in atherogenesis. In addition, there is also emerging knowledge that the eCB system has an important role in atherogenesis. We will attempt to integrate oxidative stress and the eCB system into a conceptual framework that provides insights into this pathology.